Uscire dalla crisi finanziaria statunitense: la politica domina l’economia nella Nuova Economia Politica.(Resolving the US Financial Crisis: Politics Dominates Economics in the New Political Economy) - Jan Kregel (Moneta e Credito, 2011)
Most economists expected that the “Great Recession” produced by the financial meltdown of 2008 would usher in a resurgence of traditional Keynesian economics and a decline of what has come to be called “market fundamentalism”. By contrast, also due to the inadequate size of the 2009 stimulus package, the resurgence of support for Keynesian expenditure policies has been extremely short lived. However, the negative popular and political reaction should not have come as a surprise, at least for three reasons: the design of the Obama stimulus plan and its difference from the expenditure policies of the Roosevelt Administration; the political environment that has eviscerated fiscal policy and placed monetary policy at the centre of economic policy and produced “debt driven” growth; the difference between policies appropriate to treating an income deflation and a debt deflation.